The kinetics of force-induced cell reorganization depend on microtubules and actin - Goldyn, Alexandra M.; Kaiser, Peter; Spatz, Joachim P.; Ballestrem, Christoph; Kemkemer, Ralf (Cytoskeleton, 2010)
The cytoskeleton is an important factor in the functional and structural adaption of cells to mechanical forces. In this study we investigated the impact of microtubules and the acto-myosin machinery on the kinetics of force-induced reorientation of NIH3T3 fibroblasts. These cells were subjected to uniaxial stretching forces that are known to induce cellular reorientation perpendicular to the stretch direction. We found that disruption of filamentous actin using cytochalasin D and latrunculin B as well as an induction of a massive unpolarized actin polymerization by jasplakinolide, inhibited the stretch-induced reorientation. Similarly, blocking of myosin II activity abolished the stretch-induced reorientation of cells but, interestingly, increased their motility under stretching conditions in comparison to myosin-inhibited nonstretched cells. Investigating the contribution of microtubules to the cellular reorientation, we found that, although not playing a significant role in reorientation itself, microtubule stability had a significant impact on the kinetics of this event. Overall, we conclude that acto-myosin, together with microtubules, regulate the kinetics of force-induced cell reorientation. © 2010 Wiley-Liss, Inc.
Gesehen am 20.04.2023